Postnatal Unit Experiences Associated With Exclusive Breastfeeding During the Inpatient Stay: A Cross-Sectional Online Survey. (May 2022) - Tully, Kristin P.; Smith, Jacquana L.; Pearsall, Marina S.; Sullivan, Catherine; Seashore, Carl; Stuebe, Alison M.
Background: Efforts to provide accessible and effective infant feeding support are advancing to set up new families to meeting their goals. However, data continue to be limited for understanding how inpatient postpartum support and experiences contribute to exclusive breastfeeding during hospitalization. Research Aims: To explore postnatal unit experiences including skin-to-skin contact, overnight support, rooming-in, responsive clinicians, and understandable communication that correlate with early infant feeding outcomes among a sample of mothers who intended to breastfeed. Methods: This was a prospective cross-sectional survey study. Through secure online survey, participants submitted ( N = 2, 401) responses from November 2016 to May 2017 about their experiences with maternity healthcare and offered thoughts on the postnatal unit environment. Descriptive statistics were used to examine distributions of maternal characteristics, postpartum experience, and birthing facility characteristics. Results: Exclusive breastfeeding was positively correlated with the following postnatal unit experiences: mother did not ask that her infant be taken out of the postnatal unit room; infant staying in postnatal unit room except for treatment(s); mother got help from clinical staff when needed after pressing the call button; and nurse, midwife, and/or doctor always explained information to mother in ways that they understood. Conclusion: Postnatal unit experiences associated with exclusive breastfeeding during postpartum hospitalization were rooming in; parents who did not ask for their infant to be taken out of the unit room; whether mothers received timely help from clinical staff; and information was explained in a way they could understand.